Quantitative and qualitative assessment of plasma cell dyscrasias in dual-layer spectral CT - Brandelik, Simone Christine; Skornitzke, Stephan; Mokry, Theresa; Sauer, Sandra; Stiller, Wolfram; Nattenmüller, Johanna; Kauczor, Hans-Ulrich; Weber, Tim; Do, Thuy (European radiology, 2021)
Objectives Virtual non-calcium (VNCa) images could improve assessment of plasma cell dyscrasias by enhancing visibility of bone marrow. Thus, VNCa images from dual-layer spectral CT (DLCT) were evaluated at different calcium suppression (CaSupp) indices, correlating results with apparent diffusion coefficient (ADC) values from MRI. - Methods Thirty-two patients with initial clinical diagnosis of a plasma cell dyscrasia before any chemotherapeutic treatment, who had undergone whole-body low-dose DLCT and MRI within 2 months, were retrospectively enrolled. VNCa images with CaSupp indices ranging from 25 to 95 in steps of 10, conventional CT images, and ADC maps were quantitatively analyzed using region-of-interests in the vertebral bodies C7, T12, L1-L5, and the iliac bone. Independent two-sample t-test, Wilcoxon-signedrank test, Pearson’s correlation, and ROC analysis were performed. - Results Eighteen patients had a non-diffuse, 14 a diffuse infiltration in conventional MRI. A significant difference between diffuse and non-diffuse infiltration was shown for VNCa-CT with CaSupp indices from 55 to 95, for conventional CT, and for ADC (each p < 0.0001). Significant quantitative correlation between VNCa-CT and MRI could be found with strongest correlation at CaSupp index 65 for L3 (r = 0.68, p < 0.0001) and averaged L1-L5 (r = 0.66, p < 0.0001). The optimum CT number cut-off point for differentiation between diffuse and non-diffuse infiltration at CaSupp index 65 for averaged L1-L5 was −1.6 HU (sensitivity 78.6%, specificity 75.0%). - Conclusion Measurements in VNCa-CT showed the highest correlation with ADC at CaSupp index 65. VNCa technique may prove useful for evaluation of bone marrow infiltration if MRI is not feasible. Key Points • VNCa-CT images can support the evaluation of bone marrow infiltration in plasma cell dyscrasias. • VNCa measurements of vertebral bodies show significant correlation with ADC in MRI. • Averaging L1-L5 at CaSupp index 65 allowed quantitative detection of infiltration comparable to MRI ADC.
Gesehen am 17.10.2023